Pengaruh Debt Covenant, Company Growth, Invesment Opportunity Set dan Dividend Payout Ratio Terhadap Konservatisme Akuntansi - Riani, Desmy; N.A. Rumiasih, N.A. Rumiasih; Ratnawati, Dini; Maulani, Denia (Kompartemen : Jurnal Ilmiah Akuntansi, 2023)
The purpose of this study is to analyze the effect of Debt Covenant, Company Growth, Investment Opportunity Set and Dividend Payout Ratio on Accounting Conservatism in Finance companies in the banking sub-sector listed on the Indonesia Stock Exchange in the 2016-2021 period. The determination of the sample uses the purposive sampling method, which is a sampling method based on predetermined criteria. The technical data analysis used is descriptive statistical analysis and multiple linear regression analysis using Eviews 12. The result of this study is that the data shows that partially company growth has a positive and significant effect, the investment opportunity set has no negative and significant impact. The debt covenant and dividend payout ratio have no effect and are not significant to accounting conservatism. And simultaneously independent variables are influential and significantly absorb accounting conservatism.